Impact of the COVID-19 pandemic on complications of tooth injuries. Cross-sectional retrospective study - Carolina Ainelén, Simón (2022)
Objective: evaluate the presence of complications of dental trauma due to the lack of controls resulting from confinement by COVID-19.  Materials and Methods: Retrospective cross-sectional study of patients with dental trauma who consulted the residence service of the dental center (OSEP), Province of Mendoza in a period of 3 months, prior to the official declaration of social, preventive and compulsory isolation in Argentina. The sample obtained was 27 patients who met the inclusion criteria. An analysis of data from medical records, radiographic studies and pulp sensitivity tests was performed. Results: The most prevalent trauma was enamel and dentin fracture without involvement of supporting tissues. From the data obtained, the antero-superior teeth were identified as the most affected. A higher frequency was observed in the age groups from 7 to 15 years, with a predilection for males. The emergency treatment was related to the initial diagnosis. Pulp necrosis was the most frequent post-traumatic complication in all types of dental trauma, and inflammation/fistula, periapical lesion, pain, calcification, discoloration, mobility and loss of the affected tooth were also observed. Conclusion: The pandemic had consequences in the follow-up and timely treatment of traumatized patients, generating the appearance of unfavorable complications